Anorectal Malformation: An Atypical Association of Pierre Robin Sequence - Manal M. Farouk; Sherif N. Kaddah; Magd Ahmed Kotb (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Isolated Pierre Robin sequence (PRS) is characterized by underdeveloped jaw, backward displacement of the tongue and upper airway obstruction with or without cleft palate or be part of a known syndrome as VACTREL or CHARGE, or be associated with other malformations as congenital heart disease, lung malformations, musculoskeletal system anomalies, and hereditary progressive arthro-ophthalmopathy. We report a neonate with PRS who presented by choanal atresia, sepsis, single ventricle, large ventricular septal defect; large patent ductus arteriosus, anorectal malformation in the form of high imperforate anus and rectovesical fistula. Anorectal malformation was not previously reported in Pierre Robin sequence. We report that single ventricle and anorectal malformation are rare associations of PRS. Examination for anorectal malformation, prompt diagnosis and initiation of specific management is life-saving in any neonate and especially in those with structural malformations or deformities of PRS.